Behavior of eccentrically loaded rectangular RC columns wrapped with CFRP jackets under different preloading levels. (February 2021) - Wang, Jizhong; Lu, Shiwei; Yang, Junlong
Abstract: Due to service loads during the FRP strengthening procedure in practical engineering, existing RC columns are subjected to a critical compression stress, which indicates that the effect of preload on the confinement provided by FRP composites should be considered. Against this background, an experimental investigation was performed to explore the performance of eccentrically loaded rectangular RC columns with different CFRP strengthening schemes and preloading levels. The results show that the load-bearing capacity and ultimate deformations of the specimens can be significantly enhanced after CFRP strengthening. In specific, the full wrapping strategy was more effective than CFRP strips for columns under a small eccentricity, while increasing the number of longitudinal CFRP layers on the tensile side of the specimens can achieve better strengthening effect for specimens under a large eccentricity. Moreover, the preload was found to have a detrimental effect on the load-bearing capacity and ductility of the specimens. Finally, a new stress-strain model of FRP-confined concrete considering the preload effect was proposed based on a collected database from the relevant literature. The axial load and bending moment capacity of the selected columns were calculated by using different stress-strain models; comparisons between the experimental observations and theoretical calculations revealed that better performance can be achieved by the proposed model. Highlights: The eccentric compressive behavior of rectangular preloaded RC columns wrapped with FRP sheets was investigated. The preloading had a detrimental impact on the mechanical performance of FRP wrapped columns. A new stress-strain model for FRP confined preloaded concrete was proposed. The theoretical predictions of axial load and bending moment capacity were presented.